Social Media Marketing and Consumer Behaviour (International Journal of Latest Technology in Engineering Management & Applied Science, 2026)
The rapid growth of social media platforms has transformed the marketing landscape, enabling businesses to engage directly with consumers through interactive and personalized communication. Social media marketing (SMM) has become a critical strategy for influencing consumer awareness, attitudes, purchasing decisions, and brand loyalty. This research article examines the relationship between social media marketing and consumer behaviour by reviewing existing literature and analyzing the impact of social media platforms on consumer decision-making. The study identifies key factors such as electronic word-of-mouth (eWOM), influencer marketing, online reviews, content quality, customer engagement, and personalization that significantly influence consumer behaviour. The findings suggest that effective social media marketing enhances customer trust, satisfaction, and long-term brand relationships. The article concludes with implications for marketers and recommendations for future research.